Religiusitas dan Psychological Wellâ€Being Pada Korban Gempa - Amawidyati, Sukma Adi Galuh; Utami, Muhana Sofiati (Jurnal Psikologi, 2007)
The purpose of this study is to examine the correlation between religiousity and psychological wellâ€being on earthquake survivor at Yogyakarta. Several studies show that religiousity give some benefits to reach wellâ€being. Both of variables are measured by Psychological Wellâ€Being Scale and Religiousity Scale. The result shows there is positive correlation between religiousity and psychological wellâ€being(r=0, 505; p